2017
DOI: 10.5152/tud.2017.61257
|View full text |Cite
|
Sign up to set email alerts
|

Single session vs two sessions of flexible ureterosopy (FURS) for dusting of renal pelvic stones 2-3 cm in diameter: Does stone size or hardness play a role in number of sessions to be applied?"

Abstract: Objective: To evaluate the stone hardness in predicting the need for single or two sessions of retrograde intrarenal surgery (RIRS) for renal pelvis stones of 2-3 cm in size. Material and methods:Ninety-six patients (64 male and 32 female) with only renal stones (2.5±0.3 cm) underwent RIRS using flexible 7.5 Fr ureteroscope (FURS). The stone hardness was evaluated by preoperative non-contrast computed tomography (NCCT). The patients were divided into two groups based on stone hardness: Group I (n=54) (hard sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
(33 reference statements)
1
7
1
1
Order By: Relevance
“…14 Interestingly, Abd el Hamed et al, showed that the SFR following a single session of RIRS for management of 2-3 renal stones, was 67%; however, when they analyzed the patients based on the stone density, the SFR was 95 vs 40% for patients with HU of ˂1000 and ˃1000, respectively. 15 Our results supported these findings, where only 38.7% of patients in the current series had stones with HU ˃1000 and the SFR for this group of patients was 50% compared to 89.9% for stones with HU of ˂1000. Likewise, a systematic review of the studies considering RIRS for the management of large renal stones >2.5 cm, demonstrated a SFR of 89.3%, which is higher than the SFR in our series.…”
Section: Discussionsupporting
confidence: 89%
“…14 Interestingly, Abd el Hamed et al, showed that the SFR following a single session of RIRS for management of 2-3 renal stones, was 67%; however, when they analyzed the patients based on the stone density, the SFR was 95 vs 40% for patients with HU of ˂1000 and ˃1000, respectively. 15 Our results supported these findings, where only 38.7% of patients in the current series had stones with HU ˃1000 and the SFR for this group of patients was 50% compared to 89.9% for stones with HU of ˂1000. Likewise, a systematic review of the studies considering RIRS for the management of large renal stones >2.5 cm, demonstrated a SFR of 89.3%, which is higher than the SFR in our series.…”
Section: Discussionsupporting
confidence: 89%
“…The success rate for FURS may depend on many factors, such as the location of stone, size, density, years, gender, side and BMI. Pervious, One study showed that the total average operating time in the hard stones group was significantly longer [27]. However, in our study, the results were compared between the LDS group and the HDS group, showing that the total operating time in the LDS group is significantly longer.…”
Section: Discussioncontrasting
confidence: 58%
“…FURS has been gradually accepted by patients and doctors in the treatment of larger renal stones (≧2 cm) as it can achieve a satisfactory free stone rate but rarely complications [27]. Because of some patients who cannot tolerate PCNL, the introduction of a new generation of YAG laser or thulium fiber laser and the development of endoscopic technology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, minimally invasive treatment modalities including miniaturized percutaneous nephrolithotomy (mPNL) and flexible ureterorenoscopy (f‐URS) are widely performed with acceptable stone‐free and complication rates. The combination of modern flexible ureterorenoscopes and holmium laser assure effective stone fragmentation while using natural orifices [3]. Other size, access through 14F–20F is called mPNL and mPNL provides less hemorrhagic complications and postoperative morbidity compared with conventional percutaneous nephrolithotomy (cPNL) [4].…”
Section: Introductionmentioning
confidence: 99%